THE APPLICATION OF CLASS CGM MODEL ON THE PEANUT PLANTS (Arachis Hypogaea L.) - Afina Afina; Indarto Indarto; Idah Andriyani (UPT Penerbitan Universitas Jember, 2012)
The purpose of this research is to learn the working process of CGM model and to compare the water content value of model simulation with field observation. This researchwas done in the form of experiment. The parameters of the observation were the soilphysical observations, they are: the analysis of soil (soil texture), the analysis of bulkdensity (BV), the measurement of soil water content (KA) every 10 days, and themeasurement of the thickness of the soil layer. The calculation of the model then comparedwith the result of field measurements. The results showed that the texture of the soil layer 1and layer 2: sandy clay loam and layer 3: sandy loam. The grafic comparison of simulatedsoil water content (KA) and the observation indicates that the simulation model of watercontent value (KA) increases the decline in value. Meanwhile the value of water contentobservation of layer 1 is always over the water content of layer 2 and 3. This is influencedby soil texture factor in each layer of the peanut plants land, because the texture of the soilalso determines a water system in the soil like infiltration rate, rainfall, and water bindingability of the soil. Further research is necessary to observe the growth of plants as a resultof the water content of the soil and to compare with the results of a model simulations.